Correlation Between Static and Dynamic Collapse of Compressed Thin-Walled Tubes - Molnar, C. (Engineering Transactions, 1981)
Static and dynamic crush tests on a thin-walled prismatic column are described taking into account imperfections. The crushing process is regarded as a stochastic one and the results of measurements are reduced using the probability methods. Three different definitions of the mean dynamic crushing force are discussed and only one of these is shown to yield simple and reliable results. The correlation between the static and dynamic crushing force is also presented. The results obtained may be used in designing energy-absorbing supporting structures for bus safety bumpers.